Analisis Blank Area pada Pancaran Radar MSSR di Airnav Tanjungpinang Akibat adanya Obstacle yang Menghalangi Pancaran Radar - Muhammad Caesar Akbar; Christian Simamora (Politeknik Penerbangan Makassar, 2022)
The history of radar development dates back to the late 1940s, radar has been integrated into air traffic control systems. Since then much progress has been made in both equipment and procedures that today's radar performs far better than it was originally envisioned a few years ago. Radar equipment is now installed in almost all air traffic control units around the world. The radar system is very helpful for air traffic control personnel, namely maintaining the safety, smoothness and orderliness of air traffic.The existence of radar for the first time was the idea of ​​two German scientists, namely Heinrich and Christian Hulsmeyer, in 1922. Experiments were carried out by the two scientists and then they were able to practice in the field. They use it to avoid collisions between ships in the ocean. From there it finally led to the development of radar. The radar system was first used in 1925 by Gregory Briet and Merle A. Tune of America.